Effect of ampoule support on the growth of organic benzimidazole single crystals by vertical Bridgman technique for nonlinear optical applications. Issue 25 (25th May 2016) - Krishna, Anuj; Vijayan, N.; Bagdia, Chandan; Thukral, Kanika; Sonia,; Haranath, D.; Maurya, K. K.; Bhagavannarayana, G.
Abstract : Benzimidazole single crystals with enhanced crystalline perfection and optical transparency were grown using a vertical Bridgman technique with modified ampoule design. Abstract : Benzimidazole single crystals were grown using a vertical Bridgman technique with modified ampoule design. The thermal fluctuations during the melt were effectively controlled by the glass ampoule support which was filled with alumina wool in order to maintain a proper temperature gradient throughout the growth process. The unit cell dimensions of the grown crystals were assessed using powder X-ray diffraction technique. Comparative analyses have been carried out for both the crystals which were grown using a conventional ampoule and using the ampoule with support, via high resolution X-ray diffraction and it was found that there was a significant enhancement in crystalline perfection for the crystal which was grown using the ampoule with support. Further, optical transmission and photoluminescence studies on the grown crystals were carried out using UV-vis and photoluminescence spectroscopy and it was observed that there was a noticeable variation in the optical transmission and luminescence results.